The fractal analysis in q space for the phase morphology of polypropylene/polydecamethylene sebacamide blends during melt mixing. (October 2015) - Huang, Zihan; Yan, Li-Tang; Ma, Gui-Qiu; Sheng, Jing
The fractal behavior in q space of polypropylene with polydecamethylene sebacamide (Nylon1010, PA1010) (90/10 vol%) blends during melt mixing is investigated, where q is the scattering wave vector. The relation between the small-angle laser scattering image and the power spectrum of the binarized scanning electron microscopy image is discussed. Two fractal dimensions, i.e. D 1 and D 2, are deduced in q space. The results show that the fractal dimensions are effective parameters to characterize the dynamics of the phase dispersion during melt mixing. D 1 can be used to characterize the spatial fluctuation of the phase structure. With the increasing D 1, the spatial fluctuation of the phase structure becomes bigger. And D 2 can directly characterize the dispersion degree of the dispersed phase. Higher phase dispersion degree corresponds to bigger D 2 . The results indicate that these two fractal dimensions in q space have almost the same changing rule with the increasing mixing time. Both of them change considerably at the initial stage but, are almost unchanged after 2 min, demonstrating that the phase structure mainly forms at the initial stage during melt mixing.